Indoglish as A Sociolinguistic Phenomenon: The Power of Language In the 4.0 Era - Ni Ketut Putri Nila Sudewi; Muhlisin; Ardiyati, Syafira Mahfuzi (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research is aimed at identifying the linguistic level of the Indoglish phenomenon commonly used for communication in the industry 4.0 era, identifying the reasons for speakers when using Indoglish in social media, especially on Twitter, Instagram, and TikTok; and analyzing the impacts of its usage on the speakers. The data source in this study uses various forms of authentic tweets and captions that focus on the emergence of Indoglish in this era which was collected by note-taking and observation techniques. Then the data was analyzed and presented qualitatively using the theories proposed by Weinrich (1963) and Holmes (2013). The results of this research imply the forms of Indoglish linguistic level used for communication in social media, especially on Twitter, Instagram, and TikTok in three different levels, such as word level, phrase level, and clause/sentence level. Most teenagers in the 4.0 era use Indoglish language in their tweets or captions on social media to make them easier when conveying intentions for intimacy, developing closeness, affirm intentions, and expressing resentment. The impact of using this language in their communication would help them to develop their English abilities.